Evaluation of the effectiveness of bedaquiline and delamanid treatment among children and adolescents with multi-drug-resistant pulmonary tuberculosis - M.I. Sakhelashvili; I.L. Platonova; O.I. Sakhelashvili-Bil; Z.I. Piskur (Group of Companies Med Expert, LLC, 2023)
Introduction. Against the backdrop of multiple and widespread drug resistance of Mycobacterium tuberculosis (MDR-TB), there has been a significant decline in the effectiveness of treatment of tuberculosis (TB) patients in Ukraine and globally. Therefore, in recent years, new antimycobacterial drugs, such as bedaquiline (Bdq), delamanid (Dlm) and pretomanid, have been introduced to improve treatment efficacy in adults, children and adolescents. The purpose - to study the effectiveness of complex treatment with bedaquiline (Bdq) and delamanid (Dlm) in children under 18 years old with multiple and extensively drug-resistant pulmonary TB (MDR/XDR-TB). Materials and methods. To study the clinical efficacy of chemotherapy with Bdq and Dlm, a retrospective cohort analysis of medical records was conducted. The main group consisted of 40 children with MDR/XDR-TB who received comprehensive antimycobacterial therapy with Bdq and Dlm; and the control group consisted of 27 patients who received treatment without Bdq and Dlm. Results. It was found that during the first three months of treatment, there was a decrease in bacilli in all patients treated with Bdq and Dlm and in the group of patients without these new drugs (control), but in the control group, the decrease was significantly slower, p<0.05. According to the immune system parameters, after the intensive phase was completed, the activity of a specific process was 1.7 times more frequent in patients of the control group than in the main group. After completion of the course of treatment, all patients in the main group showed resorption of infiltration, compaction of foci, and formation of fibrosis in the lungs according to the results of X-ray tomographic examination. However, in 14.8% of patients in the control group, treatment failure was noted with the resumption of bacterial release and destruction in the lung tissue, and in the main group, all patients had healing of the decay cavities. In the majority (77.5%) of patients in the main group, treatment resulted in the formation of small residual changes, but large residual changes were 2.3 times more common in the control group in the form of multiple dense foci, fibrosis and residual decay cavities. Conclusions. Studies have shown the high efficacy of complex treatment with Bdq and Dlm in children and adolescents. In particular, in MDR/XDR-TB patients treated with Bdq and Dlm, treatment results were 2 times more likely to be considered "cured" than in the control group, and 1.5 times less likely to be considered "complete". The treatment success rate in the main group was 100.0%, and in the control group - 85.2%. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.